The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2015
DOI: 10.1016/j.theriogenology.2015.04.019
|View full text |Cite
|
Sign up to set email alerts
|

Proteomics of endometrial fluid after dexamethasone treatment in mares susceptible to endometritis

Abstract: Corticotherapy is a common treatment in mares susceptible to endometritis. Isoflupredone improves pregnancy rates and affects the protein profile of endometrial fluid in comparison to untreated mares. Dexamethasone decreases postbreeding fluid accumulation and uterine edema; however, its effects on the protein profile of the endometrial fluid have not yet been studied. The aim of the present study was to verify the effect of dexamethasone on the protein profile of endometrial fluid, in the presence or absence … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 44 publications
2
8
0
Order By: Relevance
“…We recognize that our ability to identify significant differences for other identified proteins was limited by the small number of mares in the study and the overabundance of some proteins in these flush samples. The availability of mares meeting our endometritis exclusion criteria was a limiting factor, but the sample size of the current study is comparable to previous studies on uterine proteomics in mares (Arlas et al, ; Smits et al, ; Wolf et al, ). Depletion of abundant proteins can improve sensitivity of proteomic analysis and might become useful for some low‐abundance proteins that have diagnostic application.…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…We recognize that our ability to identify significant differences for other identified proteins was limited by the small number of mares in the study and the overabundance of some proteins in these flush samples. The availability of mares meeting our endometritis exclusion criteria was a limiting factor, but the sample size of the current study is comparable to previous studies on uterine proteomics in mares (Arlas et al, ; Smits et al, ; Wolf et al, ). Depletion of abundant proteins can improve sensitivity of proteomic analysis and might become useful for some low‐abundance proteins that have diagnostic application.…”
Section: Discussionsupporting
confidence: 66%
“…The study indicated a differential expression of 119 proteins around the time of MRP in mares, including upregulation of several inhibitors of prostaglandin synthesis. Changes in the uterine fluid proteome have also been reported after corticotherapy in mares with endometritis (Arlas et al, ; Wolf, Maslchitzky, Gregory, Jobim, & Mattos, ).…”
Section: Introductionmentioning
confidence: 86%
“…A reduction of pro-inflammatory IL1β, CXCL8, and SAA and suppression of inflammatory mediators, such as COX-2, lipo-oxygenase 5, and NO, were reported after dexamethasone therapy, while an increase in the inflammatory modulating and anti-inflammatory IL6, IL10, and IL1RN was also observed after treatment [33]. Additionally, the administration of dexamethasone altered the production of acute-phase proteins following bacterial challenge [295] and did not alter the phagocytic function of blood-derived PMNs [296], which could predispose the mare to a secondary infection. This alteration in the acute phase protein profile has also been noted following treatment with prednisolone [297].…”
Section: Immunomodulatory Agentsmentioning
confidence: 96%
“…However, mares with a history of excessive post-breeding inflammation had significantly higher pregnancy rates when treated with acetate 9-a-prednisolone (0.1mg/kg) twice daily when compared to control cycles (Dell'Aqua et al 2004). An effect of corticosteroids on the innate uterine immune response as well as the uterine environment has been reported by several authors , Arlas et al 2015. Although the immune modulation appears to favor resolution of inflammation, it does not mimic that of resistant mares.…”
Section: Corticosteroidmentioning
confidence: 95%